Worksheet Implementation for Engaging Students in Learning - Unissa, Azeem; Teja, Sai; Priya, Vishnu (Journal of Engineering Education Transformations, 2018)
MEAs (Model-Eliciting Activities) are open-ended modelling problems that challenge students to solve complex derivations with realistic applications (Miss Kelsey Joy Rodgers, et all, 2012). . One of the tough challenges, instructor is facing now a days is creating interest among engineering students to solve a derivation, who generally feel it difficult. It is also difficult to engage students in class immediately after lunch. The main aim of this activity is to engage students and create interest among them to derive an equation. In this paper we discussed on how to overcome those problems by using a simple in classroom activity. The method used to carry out this activity is worksheet implementation. Here, the students after participating are expected to show more interest in such regular activities as they found it helpful and also interesting. Positive result is expected at the end.